2019
DOI: 10.1002/bjs.11205
|View full text |Cite
|
Sign up to set email alerts
|

Management of incidental gallbladder cancer in a national cohort

Abstract: Background Incidental gallbladder cancer is a rare event, and its prognosis is largely affected by the tumour stage and treatment. The aim of this study was to analyse the management, treatment and survival of patients with incidental gallbladder cancer in a national cohort over a decade. Methods Patients were identified through the Swedish Registry of Gallstone Surgery (GallRiks). Data were cross‐linked to the national registry for liver surgery (SweLiv) and the Cancer Registry. Medical records were collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 39 publications
3
35
0
Order By: Relevance
“…Although international guidelines recommend radical cholecystectomy for all iGBC patients, except those with T1a disease, the management of T1b iGBC remains controversial. Results from the literature are conflicting; some studies do not report a survival benefit, [22][23][24] whereas other series show an increase in 5-year survival of up to 30% after radical cholecystectomy. 25,26 Interestingly, although a general survival benefit was shown across the entire reresected cohort, patients with T1b disease did not show superior survival after re-resection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although international guidelines recommend radical cholecystectomy for all iGBC patients, except those with T1a disease, the management of T1b iGBC remains controversial. Results from the literature are conflicting; some studies do not report a survival benefit, [22][23][24] whereas other series show an increase in 5-year survival of up to 30% after radical cholecystectomy. 25,26 Interestingly, although a general survival benefit was shown across the entire reresected cohort, patients with T1b disease did not show superior survival after re-resection.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent publication from Sweden, 121/201 (60%) non-metastatic iGBC patients received a re-resection. 24 In 27 (13%) of all patients, a re-resection was not performed due to comorbidities. Another study included 218 iGBC patients and reresection was attempted in 188 (86%) patients.…”
Section: Discussionmentioning
confidence: 99%
“…Cholecystectomy alone is not recommended to treat T2 GBC since several studies have shown that re‐resection is associated with improved survival [9,10]. A residual disease is a strong prognostic factor after re‐resection [10]. Two of our three patients could be retransplanted to remove potentially residual cancer cells.…”
Section: Variables Case 1 Case 2 Casementioning
confidence: 99%
“…The main argument for routine submission of the gallbladder specimen is that not all incidental gallbladder cancers have visible macroscopic abnormalities and patients with undiagnosed disease will be deprived of additional treatment 1, 6,7 . To improve survival, current evidence 8,9 supports reresection, including liver resection and lymph node dissection for T1b, T2 and T3 gallbladder cancer. For patients with Tis and T1a incidental cancers, cholecystectomy appears to suffice [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%